y=(x)(x)(x+3)(x)(x-4)(x-12) of I wrote that correctly... man this is gonna be a pain... (x)(x) = x^2 (x^2)(x+3) = x^3 + 3x^2 (x^3 + 3x^2)(x) = (x^4 + 3x^3) (x^4 + 3x^3)(x-4) = (x^5 - 4x^4 + 3x^4 - 12x^3) put like terms together = (x^5 - x^4 - 12x^3) (x^5 - x^4 - 12x^3)(x-12) = re arrange to make easier (x-12)(x^5 - x^4 - 12x^3) = (x^6 - x^5 - 12x^4 - 12x^5 + 12x^4 + 144x^3) combin like terms x^6 - 13x^5 + 144x^3 (-12 + 12 cancels out the x^4) x^6 - 13x^5 + 144x^3 is your final answer! I really hope I did this right... I did this in my head... my method is correct, hoping my algebra is correct too was too lazy to get a paper + pencil so I worked it out in my head